Crosslinked graft copolymer and preparation method and application thereof
Through cross-linking graft copolymer technology, combining lignin sulfonate and proanthocyanin, the contradiction between environmental protection and temperature resistance of drilling fluid viscosity reducing agent is solved, and it provides an effective viscosity reduction and environmentally friendly at high temperatures. Solution for water-based drilling fluid.
Patent Information
- Application Number
- CN202310705028.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-06-14
AI Technical Summary
The existing drilling fluid viscosity reducing agents are difficult to take into account both environmental protection and temperature resistance. Traditional modified lignin viscosity reducing agents have better environmental protection but insufficient temperature resistance, while synthetic polymer viscosity reducing agents have higher temperature resistance but biodegradable Poor performance and difficult to meet the requirements of high-temperature deep well drilling.
Cross-linked graft copolymer is used, and cross-linked by lignin sulfonate and proanthocyanin is cross-linked by aldehyde cross-linking agent, combined with vinyl monomer for graft copolymerization, forming high temperature resistance with excellent viscosity reduction, adsorption and environmental protection. Environmentally friendly viscosity reducing agent.
It exhibits excellent viscosity reduction performance under high temperature environment, with temperature resistance of more than 180°C, viscosity reduction rate of more than 90%, and high biotoxicity and good biodegradability. It is suitable as an environmentally friendly viscosity reduction agent for water-based drilling fluid.
Smart Images

Figure CN119143945A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drilling fluid treating agents, and in particular to a cross-linked graft copolymer and a preparation method and application thereof. Background Art
[0002] In recent years, foreign research has focused on anionic polymer viscosity reducers based on maleic anhydride (MA), sodium allyl sulfonate (AS) and 2-acrylamido-2-methylpropanesulfonic acid (AMPS), zwitterionic polymer viscosity reducers with cationic groups, and organophosphorus viscosity reducers. Domestic research on drilling fluid viscosity reducers also focuses on the modification of natural polymer materials and synthetic polymers.
[0003] In the direction of natural polymer modification, Wang Song et al. prepared the viscosity reducer PNK by graft copolymerization of lignin sulfonate and acrylamide, and treated it with metal ion complexation and sulfonation, which has a temperature resistance of over 200°C. Wei Xiaoming et al. synthesized the lignin viscosity reducer MGAC-1 by a series of modification reactions such as condensation of lignin sulfonate with formaldehyde, graft copolymerization, and metal ion complexation, which has a temperature resistance of up to 180°C. Wang Zhonghua et al. used tannic acid as the raw material, grafted copolymerization of AMPS and AA, and prepared a tannic acid graft copolymer with a temperature resistance of over 160°C. Zhang Jianyun et al. used tara tannin, an extract from tara pod powder, and treated it with sulfonation, Fe 2+ The viscosity reducing agent SMT-T was prepared by complexation, and the viscosity reducing rate can reach more than 84% at 180℃-220℃. Zhang Liming et al. used lignin sulfonic acid and tannin extracts to crosslink with formaldehyde, and the product was crosslinked with Fe 2+ The drilling fluid viscosity reducer FTLS is formed by complexation. Compared with the traditional FCLS, it has better viscosity reduction performance and temperature and salt resistance.
[0004] In the field of synthetic polymers, Huang Jinjun et al. prepared a zwitterionic viscosity reducer THIN using acrylic acid, sodium propylene sulfonate, AMPS and cationic monomers as raw materials. The temperature resistance can reach 220°C, the salt and calcium resistance are good, and the viscosity reduction effect is better than the traditional drilling fluid viscosity reducers XY-27 and FCLS. Wang Zhonghua et al. used AMPS, acrylamide, and NN-dimethylacrylamide as raw materials and adopted an oxidation-reduction initiation system to synthesize AMPS / DMAM / AM copolymer drilling fluid viscosity reducer, which has good viscosity reduction and temperature and salt resistance, and the temperature resistance is as high as 210°C. Hu Caizhi et al. prepared AA-IPPA copolymer using acrylic acid and isopropylphosphonic acid (IPPA) with good viscosity reduction performance and temperature resistance of 200°C. Long Zhu et al. studied a method for synthesizing drilling fluid viscosity reducers using AMPS, AA, and DMDAAC from alkaline pulping waste liquid as raw materials, and the product has a temperature resistance of 150°C. Luo Yue et al. used toluene and acetone as solvents, styrene and maleic anhydride as main raw materials, and synthesized sulfonated styrene-maleic anhydride polymer (SSMA), with a viscosity reduction rate of more than 40% and a temperature resistance of 150°C. Liao Jiuming et al. used poly-1,3-diamino-2-hydroxypropane and hydroxymethylphosphine as raw materials to prepare a new type of organic phosphorus viscosity reducer, which has better temperature and salt resistance than FCLS. Shao Hui et al. used L-aspartic acid as raw material to prepare a non-toxic, easily degradable green viscosity reducer, which also achieved good viscosity reduction effect, but the temperature resistance was only 120°C.
[0005] The existing drilling fluid viscosity reducers at home and abroad are mainly divided into two categories: modified natural polymers and synthetic polymers. Among them, synthetic polymer viscosity reducers have excellent temperature resistance, but are difficult to degrade, so they are not environmentally friendly enough; modified polymer viscosity reducers are mainly grafted acrylamide polymers on natural polymers such as lignin, which sacrifice some environmental performance while pursuing higher temperature resistance. At present, there is a contradiction between environmental protection and temperature resistance in drilling fluid viscosity reducers. Although traditional modified natural macromolecular viscosity reducers such as modified lignin and modified humic acid have good environmental protection, they are not resistant to temperature and cannot meet the needs of high-temperature deep well and ultra-deep well drilling. Synthetic polymer viscosity reducers have high temperature resistance, but poor biodegradability and high cost. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems that the drilling fluid viscosity reducer in the prior art is difficult to balance environmental protection and temperature resistance, and to provide a cross-linked graft copolymer and a preparation method and application thereof. The cross-linked graft copolymer can play an excellent viscosity reduction role in a high-temperature environment at the bottom of the well, is non-toxic, easily degradable, and does not cause harm to the environment. It can be used as a viscosity reducer for preparing water-based drilling fluid.
[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a cross-linked graft copolymer, which comprises: a molecular chain A from lignin sulfonate, a molecular chain B from proanthocyanidin, a connecting group C from an aldehyde cross-linking agent, a structural unit D represented by formula (1), and a structural unit E represented by formula (2); wherein the molecular chain A and the molecular chain B are connected by a connecting group C, and the connecting group C is bonded to the carbon atoms on the benzene ring contained in each of the molecular chain A and the molecular chain B; the structural unit D and the structural unit E are grafted onto the hydroxyl groups of the molecular chain A and the molecular chain B;
[0008]
[0009] Among them, R 1 , R 2 , R 3 , R 4 , R 5 and R 6 Each is independently hydrogen or a C1-C10 straight or branched chain alkyl group;
[0010] X is a C1-C10 straight or branched alkylene group;
[0011] M is hydrogen or an alkali metal.
[0012] A second aspect of the present invention provides a method for preparing a cross-linked graft copolymer, the preparation method comprising the following steps:
[0013] (1) cross-linking lignin sulfonate and proanthocyanidin through an aldehyde cross-linking agent to obtain an intermediate product;
[0014] (2) In the presence of an initiator, the intermediate product is subjected to a grafting reaction with vinyl monomer I and vinyl monomer II to obtain a cross-linked graft copolymer.
[0015] The third aspect of the present invention provides a cross-linked graft copolymer obtained by the aforementioned preparation method.
[0016] The fourth aspect of the present invention provides the use of the aforementioned cross-linked graft copolymer in water-based drilling fluid; preferably, the cross-linked graft copolymer is used as a drilling fluid viscosity reducer.
[0017] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0018] 1) The cross-linked graft copolymer of the present invention uses two natural degradable materials, lignin sulfonate and proanthocyanidin, as raw materials, so that it has the characteristics of non-toxicity, easy degradation and environmental friendliness. Lignin sulfonate is rich in sulfonic acid groups, which can make the product form a thick hydration layer on the bentonite surface of the drilling fluid, thereby dismantling the bentonite grid structure and reducing the viscosity of the drilling fluid; proanthocyanidin is rich in phenolic hydroxyl groups, which gives the product strong adsorption on the bentonite surface and is not easy to desorb at high temperature. The organic combination of these two raw materials can make the product have excellent viscosity reduction and adsorption at the same time under high temperature environment.
[0019] 2) The present invention moderately cross-links the sulfonic acid group-rich lignin sulfonate and the phenolic hydroxyl-rich proanthocyanidin through an aldehyde cross-linking agent, so that the cross-linked product has temperature resistance, adsorption, dispersibility, and environmental protection, and is particularly suitable for use as a high-temperature resistant and environmentally friendly viscosity reducer for water-based drilling fluids; by grafting and copolymerizing the two cross-linked natural macromolecules with two vinyl monomers, the temperature resistance and salt resistance can be further improved, and the adsorption performance on the bentonite surface can be enhanced.
[0020] 3) The cross-linked graft copolymer of the present invention can be used as a viscosity reducer for water-based drilling fluids, has excellent viscosity reduction performance at high temperatures, temperature resistance of more than 180°C, viscosity reduction rate of more than 90%, biological toxicity> 90000 mg / L, biodegradability BOD 5 / COD Cr >0.28. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] After extensive research, the inventors of the present invention have discovered that by moderately cross-linking sulfonic acid group-rich lignin sulfonate with phenolic hydroxyl-rich proanthocyanidins, the cross-linked product can simultaneously possess temperature resistance, adsorption, dispersibility, and environmental protection, and is particularly suitable for use as a high-temperature resistant and environmentally friendly viscosity reducer for water-based drilling fluids, thereby completing the present invention.
[0023] The first aspect of the present invention provides a cross-linked graft copolymer, which comprises: a molecular chain A from lignin sulfonate, a molecular chain B from proanthocyanidin, a connecting group C from an aldehyde cross-linking agent, a structural unit D represented by formula (1), and a structural unit E represented by formula (2); wherein the molecular chain A and the molecular chain B are connected by a connecting group C, and the connecting group C is bonded to the carbon atoms on the benzene ring contained in each of the molecular chain A and the molecular chain B; the structural unit D and the structural unit E are grafted onto the hydroxyl groups of the molecular chain A and the molecular chain B;
[0024]
[0025] Among them, R 1 , R 2 , R 3 , R 4 , R 5 and R 6 Each is independently hydrogen or a C1-C10 straight or branched chain alkyl group;
[0026] X is a C1-C10 straight or branched alkylene group;
[0027] M is hydrogen or an alkali metal.
[0028] In the present invention, examples of the C1-C10 straight or branched alkyl group may be any one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl, n-hexyl, isohexyl, n-heptyl, isoheptyl, 2-methylhexyl, 2-ethylhexyl, 1-methylheptyl, 2-methylheptyl, n-octyl, isooctyl, n-nonyl, isononyl and 3,5,5-trimethylhexyl.
[0029] In the present invention, examples of the C1-C10 straight-chain or branched alkylene group may be any one of methylene, 1,2-ethylene, n-propylene, isopropylene, n-butylene, isobutylene, n-pentylene, isopentylene, n-hexylene, isohexylene, n-heptylene, isoheptylene, 2-methylhexylene, 2-ethylhexylene, 1-methylheptylene, 2-methylheptylene, n-octylene, isooctylene and n-nonylene.
[0030] In the present invention, examples of the alkali metal include any one of Li, Na and K.
[0031] In some preferred embodiments of the present invention, M is hydrogen or sodium, more preferably hydrogen.
[0032] In some preferred embodiments of the present invention, R 1 , R 2 , R 3 , R4 , R 5 and R 6 Each is independently hydrogen or a C1-C6 straight-chain or branched alkyl group, more preferably hydrogen or a C1-C4 straight-chain or branched alkyl group; further preferably hydrogen, methyl or ethyl.
[0033] In a particularly preferred embodiment of the present invention, R in formula (1) 1 and R 2 All of them are hydrogen. In this case, the structural unit represented by formula (1) may be a structural unit derived from acrylamide.
[0034] In a particularly preferred embodiment of the present invention, R in formula (2) 3 and R 4 All are hydrogen, R 5 and R 6 All of them are methyl groups, X is a methylene group, and M is hydrogen. In this case, the structural unit represented by formula (3) may be a structural unit derived from acrylic acid-2-acrylamide-2-methylpropanesulfonic acid (AMPS).
[0035] In the present invention, the connecting group C is bonded to the carbon atoms on the benzene rings contained in the molecular chains A and B, preferably to the active carbon atoms on the benzene rings, and the active carbon atom is preferably located at the ortho position of the phenolic hydroxyl group or the sulfonic acid group and has a position that can provide bonding.
[0036] In the present invention, crosslinking includes but is not limited to: crosslinking of two molecules from lignin sulfonate by an aldehyde crosslinking agent, crosslinking of two molecules from proanthocyanidins with an aldehyde crosslinking agent, and crosslinking of a molecule from lignin sulfonate and a molecule from proanthocyanidins with an aldehyde crosslinking agent.
[0037] In the present invention, the structural unit D and the structural unit E are grafted copolymerized with the molecular chain A and the molecular chain B, wherein a free radical graft polymerization reaction occurs between the hydroxyl groups (alcoholic hydroxyl groups and / or phenolic hydroxyl groups) of the molecular chain A and the molecular chain B and the vinyl double bonds of the structural unit D and the structural unit E. That is, the structural unit D and the structural unit E are grafted onto the hydroxyl groups of the molecular chain A and the molecular chain B.
[0038] In the present invention, grafting includes but is not limited to: structural unit D is grafted on the hydroxyl group of molecular chain A, structural unit D is grafted on the hydroxyl group of molecular chain B, and structural unit D is grafted on molecular chain A and molecular chain B at the same time; structural unit E is grafted on the hydroxyl group of molecular chain A, structural unit E is grafted on the hydroxyl group of molecular chain B, and structural unit E is grafted on molecular chain A and molecular chain B at the same time; structural unit D and structural unit E are simultaneously grafted on the hydroxyl group of the molecular chain A and / or molecular chain B, and the hydroxyl group is an alcohol hydroxyl group and / or a phenolic hydroxyl group.
[0039] In the present invention, the composition and structure of the cross-linked graft copolymer can be determined by infrared, nuclear magnetic and other methods, or by raw material feeding.
[0040] In the present invention, lignin sulfonate is rich in sulfonic acid groups, which can make the product form a thick hydration layer on the bentonite surface of the drilling fluid, thereby dismantling the bentonite grid structure and reducing the viscosity of the drilling fluid; proanthocyanidins are rich in phenolic hydroxyl groups, which give the product strong adsorption on the bentonite surface and are not easy to desorb at high temperatures. After the two raw materials are organically combined, the product can have excellent viscosity reduction and adsorption properties under high temperature environments. The present invention uses lignin sulfonate and proanthocyanidins, two natural degradable materials, as raw materials, so that they have the characteristics of being non-toxic, easily degradable and environmentally friendly.
[0041] The present invention moderately crosslinks lignin sulfonate rich in sulfonic acid groups and proanthocyanidins rich in phenolic hydroxyl groups through an aldehyde crosslinking agent, so that the crosslinked product has temperature resistance, adsorption, dispersibility and environmental protection, and is particularly suitable for use as a high-temperature resistant and environmentally friendly viscosity reducer for water-based drilling fluids; and by graft copolymerizing the two crosslinked natural macromolecules with two vinyl monomers, the temperature resistance and salt resistance can be further improved, and the adsorption performance on the surface of bentonite can be enhanced.
[0042] In some embodiments of the present invention, the weight ratio of the molecular chain A to the molecular chain B is 1:0.25-4, preferably 1:0.5-2.
[0043] In some embodiments of the present invention, the ratio of the total weight of the molecular chain A and the molecular chain B to the weight of the linking group C is 10-30:1, preferably 15-25:1, and more preferably 18-22:1.
[0044] In some embodiments of the present invention, the ratio of the total weight of the structural unit D and the structural unit E to the total weight of the molecular chain A and the molecular chain B is 1:5-10, preferably 1:6-9, and more preferably 1:7-8.
[0045] In some embodiments of the present invention, the weight ratio of the structural unit D to the structural unit E is 1:0.4-2.5, preferably 1:1-2, and more preferably 1:1-1.5.
[0046] In some embodiments of the present invention, the lignin sulfonate is selected from one or more of sodium lignin sulfonate, potassium lignin sulfonate and calcium lignin sulfonate; preferably sodium lignin sulfonate and / or potassium lignin sulfonate, more preferably sodium lignin sulfonate.
[0047] In some embodiments of the present invention, the sulfonation degree of the lignin sulfonate is 0.3-1, preferably 0.6-1, and more preferably 0.8-1. The higher the sulfonation degree of the lignin sulfonate, the higher the number of sulfonic acid groups it carries, so that the product has better hydration ability and is not easy to dehydrate at high temperature, so that the cross-linked polymer has better high-temperature viscosity reduction performance.
[0048] In some embodiments of the present invention, the weight average molecular weight of the lignin sulfonate is 2000-12000 g / mol, preferably 4000-10000 g / mol, and more preferably 6000-8000 g / mol.
[0049] In some embodiments of the present invention, the proanthocyanidins are selected from one or more anthocyanin extracts of grapes, hawthorn, peanuts, ginkgo, thuja rohanata, thuja juniper, blueberries and black beans, preferably anthocyanin extracts of grapes and / or hawthorn, more preferably anthocyanin extracts of grapes.
[0050] Proanthocyanidins are a general term for a large class of polyphenolic compounds widely found in plants, and their common feature is that they can produce anthocyanidins when heated in an acidic medium. The proanthocyanidins in the present invention refer to anthocyanidin extracts extracted from the above substances.
[0051] In some embodiments of the present invention, the weight average molecular weight of the proanthocyanidins is 500-3000 g / mol, preferably 1000-2000 g / mol, and more preferably 1500-2000 g / mol.
[0052] In some embodiments of the present invention, the linking group C is selected from -CH 2 -、-CH 2 OCH 2 -、-CH(CH 3 )-、-CH(CH 3 )O(CH 3 )CH-、-CH 2 -CH 2 -One or more.
[0053] In the present invention, the linking group C that cross-links the lignin sulfonate and the proanthocyanidin can be a dimethylene bridge, for example, -CH 2 -、-CH(CH 3 )-、-CH 2 -CH 2 -; can also be a dimethylene ether bridge, for example, -CH 2 OCH 2 -、-CH(CH 3 )O(CH 3 )CH-.
[0054] In some embodiments of the present invention, the aldehyde crosslinking agent is a water-soluble low-level aldehyde, preferably selected from one or more of formaldehyde, acetaldehyde, glyoxal and glutaraldehyde, more preferably formaldehyde and / or acetaldehyde, further preferably formaldehyde.
[0055] In some embodiments of the present invention, the weight average molecular weight of the cross-linked graft copolymer is 10,000-100,000 g / mol, preferably 30,000-80,000 g / mol.
[0056] In some embodiments of the present invention, the cross-linked graft copolymer has a temperature resistance of ≥180°C, a viscosity reduction rate of 10wt% bentonite slurry of ≥90%, a biological toxicity of >90000mg / L, and a biodegradability of BOD 5 / COD Cr >0.28.
[0057] A second aspect of the present invention provides a method for preparing a cross-linked graft copolymer, the preparation method comprising the following steps:
[0058] (1) cross-linking lignin sulfonate and proanthocyanidin through an aldehyde cross-linking agent to obtain an intermediate product;
[0059] (2) In the presence of an initiator, the intermediate product is subjected to a grafting reaction with vinyl monomer I and vinyl monomer II to obtain a cross-linked graft copolymer.
[0060] In the present invention, in step (1), the aldehyde crosslinking agent is bonded to the carbon atoms on the benzene ring contained in the lignin sulfonate and the proanthocyanidin through a crosslinking reaction, preferably to the active carbon atoms on the benzene ring, and the active carbon atom is preferably located at the ortho position of the phenolic hydroxyl group or the sulfonic acid group and has a position that can provide bonding.
[0061] In the present invention, in step (2), a free radical graft polymerization reaction occurs between the hydroxyl groups (alcoholic hydroxyl groups and phenolic hydroxyl groups) in the lignin sulfonate and proanthocyanidin and the vinyl double bonds in the vinyl monomer I and the vinyl monomer II.
[0062] In the present invention, the structure and composition of the cross-linked graft copolymer can be determined by NMR, IR, GPC, elemental analysis and other measurement methods, or by the amount of raw materials added during preparation.
[0063] In some embodiments of the present invention, the weight ratio of the lignin sulfonate to proanthocyanidins is 1:0.25-4, preferably 1:0.5-2.
[0064] In some embodiments of the present invention, the total mass concentration of the lignin sulfonate and proanthocyanidins in water is 10%-40%, preferably 20%-30%.
[0065] In some embodiments of the present invention, the weight ratio of the total weight of the lignin sulfonate and proanthocyanidins to the weight of the aldehyde cross-linking agent is 10-30:1, preferably 15-25:1, and more preferably 18-22:1.
[0066] In some embodiments of the present invention, the ratio of the total weight of the vinyl monomer I and the vinyl monomer II to the total weight of the lignin sulfonate and the proanthocyanidins is 1:5-10, preferably 1:6-9, and more preferably 1:7-8.
[0067] In some embodiments of the present invention, the weight ratio of the vinyl monomer I to the vinyl monomer II is 1:0.4-2.5, preferably 1:1-2, and more preferably 1:1-1.5.
[0068] In some embodiments of the present invention, the conditions for the cross-linking reaction include: pH 3-11, preferably 4-10, more preferably 7-9; temperature 60-100°C, preferably 70-90°C, more preferably 75-85°C; time 1-4h, preferably 1.5-3h.
[0069] In the present invention, the cross-linking reaction can be carried out under acidic or alkaline conditions, and the cross-linking reaction is a covalent cross-linking reaction, in which lignin sulfonate and proanthocyanidin are covalently cross-linked by an aldehyde cross-linking agent.
[0070] In some embodiments of the present invention, the conditions of the grafting reaction include: temperature of 60-100° C., preferably 70-90° C., more preferably 75-85° C.; time of 1-4 h, preferably 1.5-3 h.
[0071] In the present invention, the grafting reaction is a graft copolymerization reaction, which is formed by connecting two different polymer chains with chemical bonds. One of them is a polymer backbone (skeleton) composed of A1 and B1 units, i.e., the main chain; the other is a polymer branch composed of D1 and E1 units, i.e., the side chain.
[0072] In some embodiments of the present invention, the weight ratio of the total weight of the lignin sulfonate and proanthocyanidins to the weight of the initiator is 100-600:1, preferably 200-500:1, and more preferably 300-400:1.
[0073] In some embodiments of the present invention, the lignin sulfonate is selected from one or more of sodium lignin sulfonate, potassium lignin sulfonate and calcium lignin sulfonate.
[0074] In some embodiments of the present invention, the proanthocyanidins are selected from one or more anthocyanin extracts of grapes, hawthorns, peanuts, ginkgo, thuja serrata, thuja serrata, blueberries and black beans.
[0075] In some embodiments of the present invention, the aldehyde cross-linking agent is a water-soluble low-level aldehyde, preferably one or more selected from formaldehyde, acetaldehyde, glyoxal and glutaraldehyde.
[0076] In the present invention, the selection of lignin sulfonate, proanthocyanidin and aldehyde cross-linking agent is the same as that of the first aspect. Please refer to the previous description for details, which will not be repeated here.
[0077] In some embodiments of the present invention, the initiator is selected from one or more of cerium ammonium nitrate, potassium persulfate and ammonium persulfate.
[0078] Specifically, the above preparation method comprises the following steps:
[0079] S1, dissolving lignin sulfonate and proanthocyanidin in water and mixing to form a solution, adjusting the pH of the solution with an alkali metal hydroxide; then heating to a specified temperature, adding an aldehyde cross-linking agent, and stirring to keep the temperature within a certain temperature range for a certain time;
[0080] S2. After the reaction is completed, vinyl monomer I and vinyl monomer II are immediately added to the reaction product obtained in step S1, and the reaction is continued at the same temperature for a certain period of time under stirring;
[0081] S3, drying the reaction product obtained in step S2 at 80-100° C. to constant weight, and then crushing and sieving the obtained solid product.
[0082] Wherein, the alkali metal hydroxide can be selected from sodium hydroxide or potassium hydroxide, preferably sodium hydroxide. The water can be selected from tap water, deionized water or distilled water, preferably deionized water.
[0083] The third aspect of the present invention provides a cross-linked graft copolymer obtained by the aforementioned preparation method.
[0084] The fourth aspect of the present invention provides the use of the aforementioned cross-linked graft copolymer in water-based drilling fluid; preferably, the cross-linked graft copolymer is used as a drilling fluid viscosity reducer.
[0085] The cross-linked graft copolymer of the present invention can be used as a high temperature resistant and environmentally friendly viscosity reducer for water-based drilling fluids, and has excellent viscosity reducing performance at high temperatures. The cross-linked graft copolymer has a temperature resistance of ≥180°C, a viscosity reducing rate of 10wt% bentonite slurry of ≥90%, a biological toxicity of >90000mg / L, and a biodegradability of BOD 5 / COD Cr >0.28.
[0086] The present invention will be described in detail below through examples.
[0087] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0088] In the following examples, the composition of the cross-linked graft copolymer obtained is determined by the feed amount of each raw material.
[0089] Method for determining biological toxicity: Determine in accordance with the "Technical Evaluation Method for Environmental Protection of Water-soluble Oilfield Chemicals" (SY / T6788-2020).
[0090] Method for determining biodegradation rate: Determine in accordance with the "Technical Evaluation Method for Environmental Protection of Water-soluble Oilfield Chemicals" (SY / T6788-2020).
[0091] Example 1
[0092] 1) Add 12.5 g of sodium lignin sulfonate (weight average molecular weight 8000, sulfonation degree 0.8), 12.5 g of proanthocyanidins (grape seed extract, weight average molecular weight 1500) and 100 g of deionized water to a three-necked flask equipped with a thermometer and a stirrer, stir until completely dissolved, and then adjust the pH to 9 with NaOH;
[0093] 2) The mixed monomer solution was heated to 80° C. in a constant temperature water bath, and then 2.78 g of formaldehyde (concentration 36%) was added, and the mixture was stirred and reacted at 80° C. for 2 h;
[0094] 3) After step 2), 2.5 g acrylamide, 2.5 g 2-acrylamido-2-methylpropanesulfonic acid and 0.016 g ammonium persulfate were added to the mixed monomer solution, and the reaction was continued at 80° C. for 4 h. After drying and crushing, a cross-linked graft copolymer A1 was obtained.
[0095] It can be known from the feeding that in the cross-linked graft copolymer A1, the molecular chain A comes from sodium lignin sulfonate, the molecular chain B comes from grape seed proanthocyanidins, the connecting group C comes from formaldehyde, the structural unit D comes from acrylamide, and the structural unit E comes from 2-acrylamido-2-methylpropane sulfonic acid; wherein, the weight ratio of the molecular chain A to the molecular chain B is 1:1; the ratio of the total weight of the molecular chain A and the molecular chain B to the weight of the connecting group C is 15:1; the ratio of the total weight of the structural unit D and the structural unit E to the total weight of the molecular chain A and the molecular chain B is 1:5; and the weight ratio of the structural unit D to the structural unit E is 1:1.
[0096] Example 2
[0097] 1) Add 20 g of sodium lignin sulfonate (weight average molecular weight 8000, sulfonation degree 0.8), 5 g of grape seed proanthocyanidins (grape seed extract, weight average molecular weight 1500) and 100 g of deionized water to a three-necked flask equipped with a thermometer and a stirrer, stir until completely dissolved, and then adjust the pH to 9 with NaOH;
[0098] 2) The mixed monomer solution was heated to 80° C. in a constant temperature water bath, and then 2.78 g of formaldehyde (concentration 36%) was added, and the mixture was stirred and reacted at 80° C. for 2 h;
[0099] 3) After step 2), 2.5 g acrylamide, 2.5 g 2-acrylamido-2-methylpropanesulfonic acid and 0.016 g ammonium persulfate were added to the mixed monomer solution, and the reaction was continued at 80° C. for 4 h. After drying and crushing, a cross-linked graft copolymer A2 was obtained.
[0100] It can be known from the feeding that in the cross-linked graft copolymer A2, the molecular chain A comes from sodium lignin sulfonate, the molecular chain B comes from grape seed proanthocyanidins, the connecting group C comes from formaldehyde, the structural unit D comes from acrylamide, and the structural unit E comes from 2-acrylamido-2-methylpropane sulfonic acid; wherein, the weight ratio of the molecular chain A to the molecular chain B is 4:1; the ratio of the total weight of the molecular chain A and the molecular chain B to the weight of the connecting group C is 15:1; the ratio of the total weight of the structural unit D and the structural unit E to the total weight of the molecular chain A and the molecular chain B is 1:5; and the weight ratio of the structural unit D to the structural unit E is 1:1.
[0101] Example 3
[0102] 1) Add 5 g of sodium lignin sulfonate (weight average molecular weight 8000, sulfonation degree 0.8), 20 g of grape seed proanthocyanidins (grape seed extract, weight average molecular weight 1500) and 100 g of deionized water to a three-necked flask equipped with a thermometer and a stirrer, stir until completely dissolved, and then adjust the pH to 9 with NaOH;
[0103] 2) The mixed monomer solution was heated to 80° C. in a constant temperature water bath, and then 2.78 g of formaldehyde (concentration 36%) was added, and the mixture was stirred and reacted at 80° C. for 2 h;
[0104] 3) After step 2), 2.5 g acrylamide, 2.5 g 2-acrylamido-2-methylpropanesulfonic acid and 0.016 g ammonium persulfate were added to the mixed monomer solution, and the reaction was continued at 80° C. for 4 h. After drying and crushing, a cross-linked graft copolymer A3 was obtained.
[0105] It can be known from the feeding that in the cross-linked graft copolymer A3, the molecular chain A comes from sodium lignin sulfonate, the molecular chain B comes from grape seed proanthocyanidins, the connecting group C comes from formaldehyde, the structural unit D comes from acrylamide, and the structural unit E comes from 2-acrylamido-2-methylpropane sulfonic acid; wherein, the weight ratio of the molecular chain A to the molecular chain B is 1:4; the ratio of the total weight of the molecular chain A and the molecular chain B to the weight of the connecting group C is 15:1; the ratio of the total weight of the structural unit D and the structural unit E to the total weight of the molecular chain A and the molecular chain B is 1:5; and the weight ratio of the structural unit D to the structural unit E is 1:1.
[0106] Example 4
[0107] 1) Add 12.5 g of sodium lignin sulfonate (weight average molecular weight 8000, sulfonation degree 0.8), 12.5 g of grape seed proanthocyanidins (grape seed extract, weight average molecular weight 1500) and 100 g of deionized water to a three-necked flask equipped with a thermometer and a stirrer, stir until completely dissolved, and then adjust the pH to 9 with NaOH;
[0108] 2) The mixed monomer solution was heated to 80° C. in a constant temperature water bath, and then 6.94 g of formaldehyde (concentration 36%) was added, and the mixture was stirred and reacted at 80° C. for 2 h;
[0109] 3) After step 2), 2.5 g acrylamide, 2.5 g 2-acrylamido-2-methylpropanesulfonic acid and 0.016 g ammonium persulfate were added to the mixed monomer solution, and the reaction was continued at 80° C. for 4 h. After drying and crushing, a cross-linked graft copolymer A4 was obtained.
[0110] It can be known from the feeding that in the cross-linked graft copolymer A4, the molecular chain A comes from sodium lignin sulfonate, the molecular chain B comes from grape seed proanthocyanidins, the connecting group C comes from formaldehyde, the structural unit D comes from acrylamide, and the structural unit E comes from 2-acrylamido-2-methylpropane sulfonic acid; wherein, the weight ratio of the molecular chain A to the molecular chain B is 1:1; the ratio of the total weight of the molecular chain A and the molecular chain B to the weight of the connecting group C is 10:1; the ratio of the total weight of the structural unit D and the structural unit E to the total weight of the molecular chain A and the molecular chain B is 1:5; and the weight ratio of the structural unit D to the structural unit E is 1:1.
[0111] Example 5
[0112] 1) Add 12.5 g of sodium lignin sulfonate (weight average molecular weight 8000, sulfonation degree 0.8), 12.5 g of grape seed proanthocyanidins (grape seed extract, weight average molecular weight 1500) and 100 g of deionized water to a three-necked flask equipped with a thermometer and a stirrer, stir until completely dissolved, and then adjust the pH to 9 with NaOH;
[0113] 2) The mixed monomer solution was heated to 80° C. in a constant temperature water bath, and then 2.78 g of formaldehyde (concentration 36%) was added, and the mixture was stirred and reacted at 80° C. for 2 h;
[0114] 3) After step 2), 1.25 g acrylamide, 1.25 g 2-acrylamido-2-methylpropanesulfonic acid and 0.008 g ammonium persulfate were added to the mixed monomer solution, and the reaction was continued at 80° C. for 4 h. After drying and crushing, a cross-linked graft copolymer A5 was obtained.
[0115] It can be known from the feeding that in the cross-linked graft copolymer A5, the molecular chain A comes from sodium lignin sulfonate, the molecular chain B comes from grape seed proanthocyanidins, the connecting group C comes from formaldehyde, the structural unit D comes from acrylamide, and the structural unit E comes from 2-acrylamido-2-methylpropane sulfonic acid; wherein, the weight ratio of the molecular chain A to the molecular chain B is 1:1; the ratio of the total weight of the molecular chain A and the molecular chain B to the weight of the connecting group C is 15:1; the ratio of the total weight of the structural unit D and the structural unit E to the total weight of the molecular chain A and the molecular chain B is 1:10; and the weight ratio of the structural unit D to the structural unit E is 1:1.
[0116] Example 6
[0117] 1) Add 12.5 g of sodium lignin sulfonate (weight average molecular weight 8000, sulfonation degree 0.8), 12.5 g of grape seed proanthocyanidins (grape seed extract, weight average molecular weight 1500) and 100 g of deionized water to a three-necked flask equipped with a thermometer and a stirrer, stir until completely dissolved, and then adjust the pH to 9 with NaOH;
[0118] 2) The mixed monomer solution was heated to 98° C. in a constant temperature water bath, and then 2.78 g of formaldehyde (concentration 36%) was added and stirred at 98° C. for 2 h;
[0119] 3) After step 2), 3.5 g acrylamide, 1.5 g 2-acrylamido-2-methylpropanesulfonic acid and 0.016 g ammonium persulfate were added to the mixed monomer solution, and the reaction was continued at 80° C. for 4 h. After drying and crushing, a cross-linked graft copolymer A6 was obtained.
[0120] It can be known from the feeding that in the cross-linked graft copolymer A6, the molecular chain A comes from sodium lignin sulfonate, the molecular chain B comes from grape seed proanthocyanidins, the connecting group C comes from formaldehyde, the structural unit D comes from acrylamide, and the structural unit E comes from 2-acrylamido-2-methylpropane sulfonic acid; wherein, the weight ratio of the molecular chain A to the molecular chain B is 1:1; the ratio of the total weight of the molecular chain A and the molecular chain B to the weight of the connecting group C is 15:1; the ratio of the total weight of the structural unit D and the structural unit E to the total weight of the molecular chain A and the molecular chain B is 1:5; the weight ratio of the structural unit D to the structural unit E is 1:0.43.
[0121] Example 7
[0122] 1) Add 12.5 g of sodium lignin sulfonate (weight average molecular weight 8000, sulfonation degree 0.8), 12.5 g of grape seed proanthocyanidins (grape seed extract, weight average molecular weight 1500) and 100 g of deionized water to a three-necked flask equipped with a thermometer and a stirrer, stir until completely dissolved, and then adjust the pH to 9 with NaOH;
[0123] 2) The mixed monomer solution was heated to 80° C. in a constant temperature water bath, and then 2.78 g of formaldehyde (concentration 36%) was added, and the mixture was stirred and reacted at 80° C. for 4 h;
[0124] 3) After step 2), 1.5 g acrylamide, 3.5 g 2-acrylamido-2-methylpropanesulfonic acid and 0.016 g ammonium persulfate were added to the mixed monomer solution, and the reaction was continued at 80° C. for 4 h. After drying and crushing, a cross-linked graft copolymer A7 was obtained.
[0125] It can be known from the feeding that in the cross-linked graft copolymer A7, the molecular chain A comes from sodium lignin sulfonate, the molecular chain B comes from grape seed proanthocyanidins, the connecting group C comes from formaldehyde, the structural unit D comes from acrylamide, and the structural unit E comes from 2-acrylamido-2-methylpropane sulfonic acid; wherein, the weight ratio of the molecular chain A to the molecular chain B is 1:1; the ratio of the total weight of the molecular chain A and the molecular chain B to the weight of the connecting group C is 15:1; the ratio of the total weight of the structural unit D and the structural unit E to the total weight of the molecular chain A and the molecular chain B is 1:5; the weight ratio of the structural unit D to the structural unit E is 1:2.3.
[0126] Example 8
[0127] 1) Add 12.5 g of sodium lignin sulfonate (weight average molecular weight 8000, sulfonation degree 0.8), 12.5 g of grape seed proanthocyanidins (grape seed extract, weight average molecular weight 1500) and 100 g of deionized water to a three-necked flask equipped with a thermometer and a stirrer, stir until completely dissolved, and then adjust the pH to 7 with NaOH;
[0128] 2) The mixed monomer solution was heated to 80° C. in a constant temperature water bath, and then 2.78 g of formaldehyde (concentration 36%) was added, and the mixture was stirred and reacted at 80° C. for 4 h;
[0129] 3) After step 2), 2.5 g acrylamide, 2.5 g 2-acrylamido-2-methylpropanesulfonic acid and 0.016 g ammonium persulfate were added to the mixed monomer solution, and the reaction was continued at 80° C. for 4 h. After drying and crushing, a cross-linked graft copolymer A8 was obtained.
[0130] It can be seen from the feeding that in the cross-linked graft copolymer A1, the molecular chain A comes from sodium lignin sulfonate, the molecular chain B comes from grape seed proanthocyanidins, the connecting group C comes from formaldehyde, the structural unit D comes from acrylamide, and the structural unit E comes from 2-acrylamido-2-methylpropane sulfonic acid; wherein, the weight ratio of the molecular chain A to the molecular chain B is 1:1; the ratio of the total weight of the molecular chain A and the molecular chain B to the weight of the connecting group C is 15:1; the ratio of the total weight of the structural unit D and the structural unit E to the total weight of the molecular chain A and the molecular chain B is 1:5; the weight ratio of the structural unit D to the structural unit E is 1:1.
[0131] Example 9
[0132] 1) Add 12.5 g of sodium lignin sulfonate (weight average molecular weight 4000, sulfonation degree 0.6), 12.5 g of proanthocyanidins (cratnathus extract, weight average molecular weight 3000) and 100 g of deionized water to a three-necked flask equipped with a thermometer and a stirrer, stir until completely dissolved, and then adjust the pH to 9 with NaOH;
[0133] 2) The mixed monomer solution was heated to 80° C. in a constant temperature water bath, and then 2.78 g of glyoxal (concentration 36%) was added and stirred at 80° C. for 2 h;
[0134] 3) After step 2), 2.5 g acrylamide, 2.5 g 2-acrylamido-2-methylpropanesulfonic acid and 0.016 g ammonium persulfate were added to the mixed monomer solution, and the reaction was continued at 80° C. for 4 h. After drying and crushing, a cross-linked graft copolymer A9 was obtained.
[0135] It can be known from the feeding that in the cross-linked graft copolymer A9, the molecular chain A comes from sodium lignin sulfonate, the molecular chain B comes from grape seed proanthocyanidins, the connecting group C comes from glyoxal, the structural unit D comes from acrylamide, and the structural unit E comes from 2-acrylamido-2-methylpropane sulfonic acid; wherein, the weight ratio of the molecular chain A to the molecular chain B is 1:1; the ratio of the total weight of the molecular chain A and the molecular chain B to the weight of the connecting group C is 15:1; the ratio of the total weight of the structural unit D and the structural unit E to the total weight of the molecular chain A and the molecular chain B is 1:5; and the weight ratio of the structural unit D to the structural unit E is 1:1.
[0136] Comparative Example 1
[0137] The method described in Example 1 was followed, except that in step 1), no proanthocyanidin was added to obtain polymer D1.
[0138] Comparative Example 2
[0139] The method described in Example 1 was followed, except that in step 1), no sodium lignin sulfonate was added to obtain polymer D2.
[0140] Comparative Example 3
[0141] The method described in Example 1 was followed, except that in step 1), acrylamide and 2-acrylamido-2-methylpropanesulfonic acid were not added to obtain polymer D3.
[0142] Comparative Example 4
[0143] Sodium ferrochrome lignin sulfonate produced by Hubei Xinrunde Chemical Co., Ltd. was used as polymer D4.
[0144] Test Case
[0145] 1) Prepare two portions of bentonite-based slurry. Add 40.0 g of bentonite for drilling fluid test slurry (in accordance with SY / T 5490) and 1.4 g of anhydrous sodium carbonate to 400 mL of distilled water. Stir at high speed for 20 min, stopping at least twice to scrape off the adhesions on the container wall, and seal and place at room temperature for 24 h.
[0146] 2) Take one portion of the bentonite base slurry and add 4.0g of sample A1 as a high temperature resistant and environmentally friendly viscosity reducer. Place the sample slurry and base slurry in a high temperature roller furnace and roll at 180°C for 16 hours. After cooling, stir at a high speed of 10000r / min for 5 minutes. Use a six-speed rotation viscometer to measure the viscosity reading of the base slurry at 100r / min. The viscosity reduction rate of sample A1 is calculated according to formula (A);
[0147]
[0148] Where:
[0149] Y——relative inhibition rate, %;
[0150] ——Base slurry reading at 100r / min;
[0151] ——Reading value containing sample slurry at 100r / min.
[0152] 3) According to steps 1) and 2), the viscosity reduction rates of viscosity reducer samples A2-A9 and D1-D4 were measured. The results are shown in Table 1.
[0153] Table 1 Measurement results
[0154]
[0155] It can be seen from the results in Table 1 that when the polymer of the present invention is added as a viscosity reducer to a 10% concentration of bentonite-based slurry and the viscosity reduction rate after high-temperature aging at 180°C for 16 hours can be as high as 90%-96%, which is much better than the iron-chromium lignin sulfonate commonly used in China, indicating that the polymer of the present invention has good viscosity reduction and temperature resistance, and can effectively improve the rheological properties of water-based drilling fluids in high temperature environments.
[0156] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A cross-linked graft copolymer, It is characterized in that The cross-linked graft copolymer comprises: a molecular chain A derived from lignin sulfonate, a molecular chain B derived from proanthocyanidin, a connecting group C derived from an aldehyde cross-linking agent, a structural unit D represented by formula (1), and a structural unit E represented by formula (2); wherein the molecular chain A and the molecular chain B are connected by the connecting group C, and the connecting group C is bonded to the carbon atoms on the benzene ring contained in each of the molecular chain A and the molecular chain B; and the structural unit D and the structural unit E are grafted onto the hydroxyl groups of the molecular chain A and the molecular chain B; Among them, R 1 , R 2 , R 3 , R 4 , R 5 and R 6 Each is independently hydrogen or a C1-C10 straight or branched chain alkyl group; X is a C1-C10 straight or branched alkylene group; M is hydrogen or an alkali metal.
2. The cross-linked graft copolymer according to claim 1, in, The weight ratio of the molecular chain A to the molecular chain B is 1:0.25-4, preferably 1:0.5-2; And / or, the ratio of the total weight of the molecular chain A and the molecular chain B to the weight of the linking group C is 10-30:1, preferably 15-25:1; And / or, the ratio of the total weight of the structural unit D and the structural unit E to the total weight of the molecular chain A and the molecular chain B is 1:5-10, preferably 1:6-9; And / or, the weight ratio of the structural unit D to the structural unit E is 1:0.4-2.5, preferably 1:1-2.
3. The cross-linked graft copolymer according to claim 1 or 2, in, The lignin sulfonate is selected from one or more of sodium lignin sulfonate, potassium lignin sulfonate and calcium lignin sulfonate; preferably sodium lignin sulfonate and / or potassium lignin sulfonate; and / or, the sulfonation degree of the lignin sulfonate is 0.3-1, preferably 0.6-1; And / or, the weight average molecular weight of the lignin sulfonate is 2000-12000 g / mol, preferably 4000-10000 g / mol.
4. The cross-linked graft copolymer according to any one of claims 1 to 3, in, The proanthocyanidins are selected from one or more anthocyanidin extracts of grapes, hawthorn, peanuts, ginkgo, thuja sutchuenensis, thuja sutchuenensis, blueberries and black beans, preferably anthocyanidin extracts of grapes and / or hawthorn; And / or, the weight average molecular weight of the proanthocyanidins is 500-3000 g / mol, preferably 1000-2000 g / mol.
5. The cross-linked graft copolymer according to any one of claims 1 to 4, in, The connecting group C is selected from -CH 2 -、-CH 2 OCH 2 -、-CH(CH 3 )-、-CH(CH 3 )O(CH 3 )CH-、-CH 2 -CH 2 -One or more.
6. The cross-linked graft copolymer according to any one of claims 1 to 5, in, The aldehyde cross-linking agent is a low-level aldehyde soluble in water, preferably one or more selected from formaldehyde, acetaldehyde, glyoxal and glutaraldehyde.
7. The cross-linked graft copolymer according to any one of claims 1 to 6, in, The weight average molecular weight of the cross-linked graft copolymer is 10000-100000 g / mol, preferably 30000-80000 g / mol; And / or, the cross-linked graft copolymer has a temperature resistance of ≥180°C, a viscosity reduction rate of 10wt% bentonite slurry of ≥90%, a biological toxicity of >90000mg / L, and a biodegradability of BOD 5 / COD Cr >0.
28.
8. A method for preparing a cross-linked graft copolymer, It is characterized in that The preparation method comprises: (1) cross-linking lignin sulfonate and proanthocyanidin with an aldehyde cross-linking agent to obtain an intermediate product; (2) In the presence of an initiator, the intermediate product is subjected to a grafting reaction with vinyl monomer I and vinyl monomer II to obtain a cross-linked graft copolymer.
9. The preparation method according to claim 8, in, The weight ratio of the lignin sulfonate to proanthocyanidins is 1:0.25-4, preferably 1:0.5-2; and / or, the total mass concentration of the lignin sulfonate and proanthocyanidins in water is 10%-40%, preferably 20%-30%; and / or, the weight ratio of the total weight of the lignin sulfonate and proanthocyanidins to the weight of the aldehyde cross-linking agent is 10-30:1, preferably 15-25:1; and / or, the ratio of the total weight of the vinyl monomer I and the vinyl monomer II to the total weight of the lignin sulfonate and the proanthocyanidins is 1:5-10, preferably 1:6-9; And / or, the weight ratio of the vinyl monomer I to the vinyl monomer II is 1:0.4-2.5, preferably 1:1-2.
10. The preparation method according to claim 8 or 9, in, The conditions of the cross-linking reaction include: pH 3-11, preferably 4-10; temperature 60-100°C, preferably 70-90°C; time 1-4h, preferably 1.5-3h; And / or, the conditions of the grafting reaction include: temperature of 60-100° C., preferably 70-90° C.; time of 1-4 h, preferably 1.5-3 h.
11. The preparation method according to any one of claims 8 to 10, in, The weight ratio of the total weight of the lignin sulfonate and proanthocyanidins to the weight of the initiator is 100-600:1, preferably 200-500:
1.
12. The preparation method according to any one of claims 8 to 11, in, The lignin sulfonate is selected from one or more of sodium lignin sulfonate, potassium lignin sulfonate and calcium lignin sulfonate; And / or, the proanthocyanidins are selected from one or more anthocyanidin extracts of grapes, hawthorns, peanuts, ginkgo, thuja sutchuenensis, thuja sutchuenensis, blueberries and black beans; and / or, the aldehyde cross-linking agent is a water-soluble low-level aldehyde, preferably one or more selected from formaldehyde, acetaldehyde, glyoxal and glutaraldehyde; And / or, the initiator is selected from one or more of ammonium cerium nitrate, potassium persulfate and ammonium persulfate.
13. The cross-linked graft copolymer obtained by the preparation method according to any one of claims 8 to 12.
14. Use of the cross-linked copolymer according to any one of claims 1 to 7 and 13 in water-based drilling fluid; preferably, the cross-linked copolymer is used as a drilling fluid viscosity reducer.
Citation Information
Patent Citations
Method for preparing biodegradable polyurethane foam by liquefied modification of bark powder and lignin
CN102675581A
Non-sulfonated viscosity reducer for drilling fluid and preparation method of non-sulfonated viscosity reducer
CN114573737A
